BOOK REVIEW: ANCA PEIU, “FAULKNERIANA. BACK TO (AND BEYOND) YOKNAPATAWPHA”, BUCUREȘTI, C.H. BECK, 2019, 266 P. - DRAGOȘ, Adina (Studia Universitatis Babeș-Bolyai Philologia, 2021)
To discuss William Faulkner in any capacity that could be considered relevant is not an easy task. As one of the most evocative authors of the American South, his novels and short stories have come to be regarded as the quintessential example of what one might call Southern literature. Moreover, his work has been spared no criticism or analysis from literary theorists and fellow authors worldwide, most of whom have made great efforts to untangle the web of themes and motifs Faulkner had become known for exploring. The translation of his work into other languages had been very significant as it had caused the resurgence of various critics and writers’ interest in Southern literature. Romania is no exception in this respect. For instance, in 1969 Sorin Alexandrescu published his study William Faulkner, Virgil Stanciu’s Orientări în literatura sudului American (1977) briefly, yet expertly delves into the Faulknerian fiction, and Mircea Mihăieș published Ce rămâne: William Faulkner și misterele ținutului Yoknapatawpha in 2012.